2021
DOI: 10.1002/joom.1152
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐item learning for volatile demand forecasting: An intervention with predictive analytics

Abstract: Despite its importance to OM, demand forecasting has been perceived as a "problem-solving" exercise; most empirical work in the field has focused on explanatory models but neglected prediction problems that are part of empirical science. The present study, involving one of the leading electronics distributors in the world, aims to improve prediction accuracy under high demand volatility for procurement managers to make better inventory decisions. In response to requests for an integrated forecasting methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 99 publications
(146 reference statements)
0
9
0
Order By: Relevance
“…A limitation is that most ML methods (including RF) are developed for independent observations and not fully calibrated for time series and panel data (Dominici et al, 2021). That said, empirical studies have shown efficacy of ML for panel data predictions (e.g., Chuang et al, 2021) and theoretical studies are thriving to show consistencies of ML estimators for longitudinal data (e.g., Medeiros & Mendes, 2016). Our hope is that our articulation of the upside of ML, abetted by clear examples meant to reduce barriers to adoption, will encourage OM scholars to apply ML methods in their research endeavors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A limitation is that most ML methods (including RF) are developed for independent observations and not fully calibrated for time series and panel data (Dominici et al, 2021). That said, empirical studies have shown efficacy of ML for panel data predictions (e.g., Chuang et al, 2021) and theoretical studies are thriving to show consistencies of ML estimators for longitudinal data (e.g., Medeiros & Mendes, 2016). Our hope is that our articulation of the upside of ML, abetted by clear examples meant to reduce barriers to adoption, will encourage OM scholars to apply ML methods in their research endeavors.…”
Section: Discussionmentioning
confidence: 99%
“…We labeled this category Supply Chain Management (SCM). We observe that ML exhibits considerable potential to generate innovative solutions to persistent SCM issues like forecast (Chuang et al, 2021), procurement (Ban et al, 2019;Mandl & Minner, 2020), and facility location (Glaeser et al, 2019). Besides traditional SCM topics, ML has been used to tackle environmental issues such as predicting violations of waste gas emission standards (Chang et al, 2021) and humanitarian logistics such as detecting sex trafficking locations (Keskin et al, 2021).…”
Section: Machine Learning In Empirical Ommentioning
confidence: 99%
See 1 more Smart Citation
“…Forecasting, machine learning models (Chuang et al, 2021;Ilk et al, 2020;Ketzenberg et al, 2020;Pak et al, 2020;Petropoulos et al, 2018) Review Reviewing the application of existing methods in OM research. An article in this class would begin with a comprehensive survey of published research, then provide a summary of issues identified, and follow up with recommendations for improvement.…”
Section: Performing Pre-review Methods Checksmentioning
confidence: 99%
“…Typically, they develop an empirical method to solve an OM problem that common techniques in the empirical toolbox do not fully address. Many studies utilizing prediction, forecasting, and machine learning models as part of their method development process naturally fit under this class (Chuang et al, 2021;Ilk et al, 2020;Ketzenberg et al, 2020;Pak et al, 2020;Petropoulos et al, 2018). Whether such research goes to a topical department or to the ERM department depends on the novelty of the method and the degree to which the contribution comes from the method rather than from the research project more generally.…”
Section: A Classification Schemementioning
confidence: 99%